2010
DOI: 10.4038/cocos.v13i0.2177
|View full text |Cite
|
Sign up to set email alerts
|

PHEROMONE BAITED TRAP FOR THE MANAGEMENT OF RED PALM WEEVIL, Rhynchophorus ferrugineus F. (Coleoptera: Curculionidae) POPULATION IN COCONUT PLANTATIONS

Abstract: 4-methyl-5-nonanol (ferrugineol), the major component of the aggregation pheromone of Rhynchophorus ferrugineus F. was evaluated as a lure for trapping of this pest in coconut plantations in Sri Lanka. Trap design, longevity of ferrugineol in field conditions, and the effect of trapping on damage incidence of R. ferrugineus were studied. N-pentanol, a known compound present in coconut stem volatiles was used in combination of ferrugineol in all tested traps. Trap designs tested were; an open plastic bucket, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…A specially designed pheromone trap was described by Maheswari & Rao (2000). Rajapakse et al . (1998) found that a 5‐L open plastic bucket baited with ferrugineol (4‐methyl‐5‐nonanol)‐pentanol, hung on coconut palm stems at 1.5 m caught significantly more adult weevils than ferrugineol‐pentanol baited funnel and metal traps.…”
Section: Detection Methodsmentioning
confidence: 99%
“…A specially designed pheromone trap was described by Maheswari & Rao (2000). Rajapakse et al . (1998) found that a 5‐L open plastic bucket baited with ferrugineol (4‐methyl‐5‐nonanol)‐pentanol, hung on coconut palm stems at 1.5 m caught significantly more adult weevils than ferrugineol‐pentanol baited funnel and metal traps.…”
Section: Detection Methodsmentioning
confidence: 99%
“…In coconut plantations in India, 1.0 m height was reported to yield highest trap catches (Faleiro, 2005). In India, Muralidharan et al (1999) hung the bucket traps on date palm trees at breast height, whereas in Sri Lanka, Rajapakse et al (1998), chose 1.5 m height above ground to hang traps on coconut trees for mass trapping studies on RPW. In Saudi Arabia, 1.5 m height was recommended for placing pheromone traps on date palm trunks .…”
Section: Stump Trapmentioning
confidence: 99%
“…During or after devouring the host, adults emerge and fly out in search of food resources and mates and cause re-infestations or newly infest the healthy palms (Nirula, 1956;Estaban-Durán et al, 1998). These outbound adults are targeted by semiochemical-based trapping methods which have been used as the mainstay of IPM programs in many countries to monitor and mass-trap the RPW populations in the field (Oehlschlager et al, 1993;Abraham et al, 1998;Rajapakse et al, 1998;Vidyasagar and Subaharan, 2000;Vidyasagar et al, 2000b;Oehlschlager et al, 2002;Soroker et al, 2005;Abbas et al, 2006;El-Sayed et al, 2006). A major advantage of RPW pheromone trapping is that it attracts nearly twice the number of females than males and thereby further helping to reduce progenies (Oehlschlager, 1998;Vidyasagar et al, 2000b;Abraham et al, 2001;Faleiro et al, 2002;Faleiro, 2005;Jayanth et al, 2007;Vacas et al, 2013Vacas et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These traps are employed both indirectly for monitoring, and directly for mass trapping (El Garhy, 1996; Gunawardena et al. , 1998; Rajapakse et al. , 1998; Abraham et al.…”
Section: Introductionmentioning
confidence: 99%